Perlakuan Akuntansi Akad Musyarakah Mutanaqisah (Studi Kasus : KPR iB Pada Bank Muamalat Cabang Darmo Surabaya) - Sarwedhie, Aishanafi Khadifya; Suprayogi, Noven (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Islamic bank is one of the services industry who offer products according to Shariah requirements. To meet the challenges and muamalah phenomena that exist in current business. Regulators, academics, practitioners, and Sharia Board are required to innovate the products that will be offered to customers. One such innovation is the emergence of hybrid contracts (multi-contract), where in the contract occurred several contract transacted. Application of the hybrid contract with the Bank Muamalah Indonesia is that using the KPR iB financing musharaka mutanaqisah contract (MMQ).Of these phenomena, this research intend to see out of the side of accounting applied in transactions using MMQ contract. This study aims to determine the accounting treatment on Musharaka mutanaqisah contract by Bank Muamalat Indonesia on KPR iB products and verify compliance whether the accounting treatment in accordance with PSAK No. 106 and DSN No. 73.The results of this research make findings that the accounting treatment was carried out by BMI for start-up capital is recognized as a capital MMQ cash. This is because the factors of positive law in force in Indonesia that have an impact on the next accounting treatment, installments process and when the end of the contract. In addition, the realization of the contract is not in harmony with the accounting treatment, so the accounting treatment can not describe what is going on in the contract because it can be obstruction by the positive law applicable. But overall accounting treatment has been carried out by BMI in accordance with PSAK No. 106 and DSN No. 73 on the MMQ installments process and when the contract expires.